Theoretical and Historical Prospective of Organizational Learning - Turi, Jamshid Ali; Sorooshian, Shahryar; Fatimah, Mahmud; Javed, Yasir (Science Publishing Corporation, 2018)
This article reviews and evaluates the concepts regarding the theoretical and historical prospective of the organizational learning. Drawing on established literature in the field of organizational learning, the authors analyze learning from three theoretical perspectives—cognitive, behavioral and social. They argue that how different internal and external phenomenon give birth to learning in organization and how the organization can benefit from them while utilizing them for the better management and productive engagement of the employees. The study concludes with some practical suggestions about how organizations can increase their ability to learn. It also describes different methods for learning and different measures.